CONTROLE ESTATÍSTICO DA QUALIDADE NA IRRIGAÇÃO POR ASPERSÃO - Frigo, Jiam Pires (2014)
The sprinkler irrigation system is widely used because of the possibility of high uniform distribution and to adapt itself to different crops and soils. On the other hand, the water uniform application in irrigation is affected by meteorological factors that decrease the system efficiency. There has always been some concern about the quality of products and services in human history, since all products should have desirable characteristics to be accepted by consumers. Currently, development, improvement and monitoring of new management models quality during the production process have become essential for many organizations. Thus, inspection control has enhanced by statistical techniques, losses have been decreased and it was possible to stimulate some trading competition. In this context, this study aimed at evaluating the irrigation system in a conventional sprinkler using the Christiansen Uniformity Coefficient (CUC) and the index Process Capability (CP) to correlate techniques with the system efficiency as well as verify the wind influence on irrigation by Shewhart control chart and compare the results of Shewhart control charts use with the EWMA and tabular CUSUM control charts, applied in quality control of the conventional sprinkler irrigation. In this study, 60 essays were carried out on a four irrigation sprinklers system, Xcel-Wobbler model, 1.0 m height above soil and 6.0 x 6.0 m spaced. The collectors were 1.0 m spaced apart with 0.5 m height from soil. The service pressure was monitored and appropriate to the sprinklers specifications, while wind was monitored in situ by a 2.0 m high digital anemometer. In order to evaluate the system, Christiansen Uniformity Coefficient (CUC), the index Process Capability (CP), Shewhart charts (Xbarra) and the charts of exponentially weighted moving average (EWMA) and cumulative sum (CUSUM) were used. The irrigation sprinkler system showed the best performance and was under control when the average wind speed was less than 1.0 m s-1. The use of individual Shewhart control charts visually allowed affirming that wind has a direct influence on CUC. Night irrigation showed less variability on the studied data, when compared to daytime ones and this has resulted in greater efficiency in irrigation. The CPi index showed great similarity with the Christiansen Uniformity Coefficient (CUC). It proved to be very sensitive to efficiency sprinkler (Ea) variation and able to indicate the quality of sprinkler irrigation. The EWMA chart, when compared to the control charts, was susceptible when used in autocorrelated data, according to the occurrence of false alarms. But, to the residue data without autocorrelation (the ARIMA model), the CUSUM tabular chart was more sensitive to detect variations in irrigation due to wind speed, when compared to EWMA and Shewhart charts for the same data. In sprinkler irrigation, when there is a relation between CUC and wind speed, the Shewhart chart was more indicated by simplicity, reliability and ease of interpretation, even in the presence of autocorrelated data.